The Impact of Gadget Use on Early Childhood in Suci Village, Manyar Sub-district - Fatmawati, Fitri Ayu (EDUTEC : Journal of Education And Technology, 2023)
The rapid development of gadgets has a significant impact, including on young children, which can lead to delays in their developmental stages. The purpose of this research is to understand the effects of gadget usage on young children. The research was conducted using a qualitative method, with the subjects being young children in the village of Suci, Manyar District, Gresik. Data for the research was gathered through observation, interviews, and documentation. The results of the research revealed that the impact of gadget usage on young children in the village of Suci has both positive and negative effects. The positive effects include facilitating communication, increasing knowledge, enhancing creativity, and aiding in the development of creativity and intelligence in children. On the other hand, the negative effects include the risk of radiation from gadgets, a decline in psychomotor skills, difficulties in adapting to learning materials, and a lack of self-control due to reduced social interactions.